Hemorrhagic fever with renal syndrome on south of far east russia: actual problems of diagnostic and treatment - V. A. Ivanis; T. V. Kushnareva; G. G. Kompanets; V. I. Verkhoturova; O. V. Iunikhina; L. Yu. Pereverten; I. G. Maksema (Журнал инфектологии, 2015)
Contemporary problems of hemorrhagic fever with renal syndrome (HFRS), being one of hantaviral infection nozoforms and wide-spread on Euro Asiatic continent are considered. Annual increase morbidity with of natural foci expansion, often severe course and a high mortality rate determine the importance of HFRS for health of many countries and in particular the Russia. This article presents of long standing results obtained during the study of epidemiologic, clinical and laboratory diagnostic, immunopathogenesis, treatment trials in Primorsky region of Russian Federation, being the endemic area of co-circulation of several pathogenic hantaviruses.